The myrmicine ant genus Metapone Forel (Hymenoptera: Formicidae): a global taxonomic review with descriptions of twelve new species - Taylor, Robert W.; Alpert, Gary D. (Zootaxa, 2016)
The 28 known species of Metapone are monographed and illustrated. Twelve are described as new: M. africana, Gabon; M. balinensis, Bali, Indonesia; M. enigmatica, northeast New Guinea; M. hoelldobleri, northeast Queensland, Australia; M. javana, Java, Indonesia; M. manni, Viti Levu, Fiji; M. mathinnae, Flinders Island, Tasmania, Australia; M. philwardi, northeast New Guinea; M. salomonis, Guadalcanal, Solomon Islands; M. tecklini, northeast Queensland; M. titan, New Ireland, Papua New Guinea; M. wallaceana, Lombok, Indonesia; spp.n. New synonymies include M. greeni Forel = M. johni Karavaiev (Sri Lanka) syn.n, and M. jacobsoni Crawley (Sumatra) = M. nicobarensis Tiwari & Jonathan (Great Nicobar Island) syn.n.